C-1 (New Delhi, 2014)
Articles 81 and 170 of the Constitution lay down the maximum number of seats in Parliament and in Legislative Assemblies of States and also certain principles to be followed in allocating seats in the House of People among the States and in the State Legislative Assemblies, but have left the actual allocation of such seats to be provided by the law. Article 171 of the Constitution lays down the maximum and minimum number of seats in the Legislative Council of a State, and also specify the various methods in which the seats shall be filled, but the actual number of seats to be filled by each such method has been left to be provided by law. In order to provide for the allocation of seats in, and the delimitation of constituencies for the purpose of election to the House of the People and the Legislatures of States, the Representation of the People Bill was introduced in the Parliament.